Unpacking the G20 Unpacking the G20 Insights from the Summit - Dobson, Hugo (Edward Elgar Publishing, 2024)
With a novel focus on the individual members of the G20, this innovative book explores the perspectives and behaviours of those within the global summit, unpacking what they are seeking to achieve, how they go about doing this, and the domestic impact of the G20.